2009
DOI: 10.1021/jm801126a
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Design of Inhibitors of Human S-Adenosylmethionine Decarboxylase: Studies of Adenine C8 Substitution in Structural Analogues of S-Adenosylmethionine

Abstract: S-Adenosylmethionine decarboxylase (AdoMetDC) is a critical enzyme in the polyamine biosynthetic pathway and depends on a pyruvoyl group for the decarboxylation process. The crystal structures of the enzyme with various inhibitors at the active site have shown that the adenine base of the ligands adopts an unusual syn conformation when bound to the enzyme. To determine whether compounds that favor the syn conformation in solution would be more potent AdoMetDC inhibitors, several series of AdoMet substrate anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 54 publications
1
39
0
Order By: Relevance
“…3A) shows similar interactions to other AdoMetDC substrate analogues (Fig. 3B) (McCloskey et al, 2009). Moreover, conformational search analysis of the N -(Z)-4-aminobutenyl- N -methyl tail of Genz-644131 showed that the lowest absolute energy of the Genz-644131 syn conformation is reached when the tail assumes the predicted binding conformation (-126.9 kcal/mol) (Fig.…”
Section: Resultssupporting
confidence: 58%
“…3A) shows similar interactions to other AdoMetDC substrate analogues (Fig. 3B) (McCloskey et al, 2009). Moreover, conformational search analysis of the N -(Z)-4-aminobutenyl- N -methyl tail of Genz-644131 showed that the lowest absolute energy of the Genz-644131 syn conformation is reached when the tail assumes the predicted binding conformation (-126.9 kcal/mol) (Fig.…”
Section: Resultssupporting
confidence: 58%
“…Finally, Wesley Brooks (Drug Discovery, Tampa, USA) reported that blocking the human S-Adenosylmethionine (SAM) Decarboxylase with a specific inhibitor prevents the SAM's degradation [28]. As a consequence this new drug should reduce the DNA methylation observed in autoimmune diseases by providing more SAM to the cell.…”
Section: New Epigenetic Therapeuticsmentioning
confidence: 99%
“…The docked model showed that AO-476/43250076 binds the enzyme with interactions similar to known inhibitors15. The scaffold of this compound is quite different from previously known AdoMetDC inhibitors131554, and therefore could represent a novel class of AdoMetDC inhibitors. The relatively low potency of this compound indicates that further optimization is necessary, and enlightened by the docking analysis of the known inhibitor in this study, a reasonable way is to add a functional group that could form a Schiff base to the active site pyruvoyl group.…”
Section: Discussionmentioning
confidence: 91%
“…S5) to confirm that the compound is indeed effective and the PEPC-MDH system is not inhibited by chance. Therefore, we feel that this assay would accelerate the discovery of novel AdoMetDC inhibitors, considering most known AdoMetDC inhibitors are based on the deoxyadenosine group1554.…”
Section: Discussionmentioning
confidence: 99%